Neuregulin 3 and Erbb Signalling Networks in Embryonic Mammary Gland Development - Kogata, Naoko; Zvelebil, Marketa; Howard, Beatrice A. (Journal of mammary gland biology and neoplasia, 2013)
We review the role of Neuregulin 3 (Nrg3) and Erbb receptor signalling in embryonic mammary gland development. Neuregulins are growth factors that bind and activate its cognate Erbb receptor tyrosine kinases, which form a signalling network with established roles in breast development and breast cancer. Studies have shown that Nrg3 expression profoundly impacts early stages of embryonic mammary development. Network analysis shows how Nrg/Erbb signals could integrate with other major regulators of embryonic mammary development to elicit the morphogenetic processes and cell fate decisions that occur as the mammary lineage is established.